Philosophical and Cognitive Aspects of Visual Metaphor in Political Discourse - Ekaterina L. Kabakhidze (RUDN Journal of Philosophy)
The postmodern doctrine of the 21st century, as well as the development of technology have changed the structure and form of the text which has increasingly acquired features of polymodality. The research aims to the study the visual metaphor, its philosophical and cognitive foundations in the political discourse exemplified in three linguacultures: American, British and Chilean. The research provides a definitional analysis of the concept of ‘visual metaphor’ and offers an overview of foreign research in the field. Cognitive aspects of visual metaphor are studied on the basis of conceptual and methodological approaches of the authors of cognitive metaphor G. Lakoff and M. Johnson, the theory of dual coding A. Paivio, philosophical reflections are based on the works of E. Cassirer, F. Nietzsche, U. Eco, R. Barth, Yu.M. Lotman. For the purpose of the present research methodology of analysis of visual metaphor with subsequent parameters were developed, which includes research methods of cognitive linguistics, semiotics and cultural studies. The presented methodology allows to analyze polymodal texts of political discourse, identify types of cognitive metaphors, analyze the structure of the sign, and reveal internal mechanisms of public opinion manipulation in the context of political discourse. The practical material of the study is represented by 30 political cartoons which were selected using the continuous sampling method, dedicated to political leaders of the USA (D. Trump), Great Britain (B. Johnson), Chile (S. Piñera) and above all are monomodal, i.e. contain only a visual code. To secure the research outcomes one more criterion to the cartoons was applied - they were supposed to depict political leaders in the metaphoric mode. The selected material was parameterized according to the developed methodology for analyzing the visual metaphor with each of the criteria described in detail. The study concludes with a comparative analysis of the visual metaphor in the political discourse of three linguacultures - American, British and Chilean - common features are highlighted, and differences are analyzed, the basis of which lie in the cultural and historical perspective, ethnic traditions.